A companion to Kazimierz Twardowski - Grądzka, Ewelina (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
There have been many significant publications on Kazimierz Twardowski. Jacek Jadacki intends to add to this list another book Rozum i wola. Kazimierz Twardowski i jego wpływ na kształt kultury polskiej XX wieku. In the review it is appraised whether it can be called “a companion to...”. It provides introductory information that can help readers better understand the role of Twardowski in Polish philosophy and culture. Updated findings by contemporary scholars are also included. The quality of the articles is guaranteed by such authors as J. Woleński, R. Kleszcz, A. Brożek and J. Jadacki. However, new authors are also present as well as less common topics like Twardowski’s influence on the Polish School of Philosophy of Medicine and his roles as political scientist, educational theorist, and historian of Ancient philosophy. The authors manage to convince the reader that Twardowski is “a classic” worth knowing, in consequence the book can be treated as a “companion to Twardowski”. It also inspires readers to further investigate the works and accomplishments of the Lvov philosopher.
Keywords: Kazimierz Twardowski; Lvov-Warsaw School; analythic philosophy; Alfred Tarski